2012
DOI: 10.1002/anie.201108245
|View full text |Cite
|
Sign up to set email alerts
|

A Secondary Sialic Acid Binding Site on Influenza Virus Neuraminidase: Fact or Fiction?

Abstract: One flu over the cuckoo's nest: The biological significance of a secondary sialic acid binding site on influenza virus neuraminidase remains elusive. On blocking the active site influenza‐virus‐containing virus‐like particles with oseltamivir carboxylate, binding to α(2,3)‐sialyllactose is still detected. Thus the sialyllactose must bind at a secondary sialic acid binding site (see structures: docking study of α(2,3)‐sialyllactose in the secondary binding site of avian flu neuraminidase).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
37
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 11 publications
6
37
0
Order By: Relevance
“…Of broader relevance, they provide a general paradigm for dynamic, catalysis-driven virus-sialoglycan interactions in relation to host selectivity. This notion is supported by observations for influenza A viruses, where neuraminidase (NA) activity toward multivalent substrates varies with differences in the length of the stalk domain and positively correlates with NA size (Castrucci and Kawaoka, 1993;Els et al, 1985), where NA catalytic activity is modulated by the absence or presence of a second Sia-binding site (Uhlendorff et al, 2009;Varghese et al, 1997) and where changes in NA stalk length and NA lectin affinity have been implicated in host specificity (Blumenkrantz et al, 2013;Castrucci and Kawaoka, 1993;Lai et al, 2012;Li et al, 2014;Matrosovich et al, 1999;Munier et al, 2010;Uhlendorff et al, 2009;Varghese et al, 1997). These observations can be readily interpreted in the context of our data and model proposed.…”
Section: Resultsmentioning
confidence: 82%
“…Of broader relevance, they provide a general paradigm for dynamic, catalysis-driven virus-sialoglycan interactions in relation to host selectivity. This notion is supported by observations for influenza A viruses, where neuraminidase (NA) activity toward multivalent substrates varies with differences in the length of the stalk domain and positively correlates with NA size (Castrucci and Kawaoka, 1993;Els et al, 1985), where NA catalytic activity is modulated by the absence or presence of a second Sia-binding site (Uhlendorff et al, 2009;Varghese et al, 1997) and where changes in NA stalk length and NA lectin affinity have been implicated in host specificity (Blumenkrantz et al, 2013;Castrucci and Kawaoka, 1993;Lai et al, 2012;Li et al, 2014;Matrosovich et al, 1999;Munier et al, 2010;Uhlendorff et al, 2009;Varghese et al, 1997). These observations can be readily interpreted in the context of our data and model proposed.…”
Section: Resultsmentioning
confidence: 82%
“…For N9, X-ray crystallography (27) revealed that the 2nd SIA-binding site is a shallow pocket composed of three surface peptide loops, located adjacent to the catalytic site. The presence of a 2nd SIA-binding site in N1 was also demonstrated using saturation transfer difference (STD) nuclear magnetic resonance (NMR) spectroscopy (28). By both hemadsorption assays and STD NMR, it was shown that N1 and N2 proteins of swine and human IAVs display severely reduced binding compared to their avian counterparts (26,28).…”
mentioning
confidence: 97%
“…The presence of a 2nd SIA-binding site in N1 was also demonstrated using saturation transfer difference (STD) nuclear magnetic resonance (NMR) spectroscopy (28). By both hemadsorption assays and STD NMR, it was shown that N1 and N2 proteins of swine and human IAVs display severely reduced binding compared to their avian counterparts (26,28). Sequence analysis indicated that five out of six SIA contact residues in the N9 2nd SIA-binding site are highly conserved across all avian NA genotypes.…”
mentioning
confidence: 99%
“…Sialic acids bind to influenza NA at two independent binding sites: the catalytic site and the secondary binding site. With the catalytic site being blocked by oseltamivir carboxylate, STD‐NMR signals of sialyllactoses binding to the secondary site could be evaluated . Differential STD‐NMR spectra were generated by subtracting the secondary site binding signals from the overall NA‐SL binding spectra, which reflect only the binding signals of sialyllactoses to the NA catalytic site.…”
Section: Resultsmentioning
confidence: 99%